Application of Cooperative Learning Methods through Sending Speeches and Questions to Improve Chemistry Learning - Islaihah, Novianti (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to find out whether the application of learning techniques for sending greetings and questions can achieve complete chemistry learning on chemical bonding material. Methodology: The instruments used in this research are tests, observation and documentation. Tests are carried out to determine student learning outcomes. Observations are carried out to determine the development of teachers and students in the ongoing learning process. Meanwhile, documentation is carried out to obtain school data, teacher data and also student data. Main Findings: Based on the results of data analysis, it was found that student learning completeness (classical) before the action was 42.5%, cycle I 47.5%, cycle II 72.5%, cycle III 87.5%, which increased with each meeting. , so it can be concluded that the application of cooperative learning techniques of sending greetings and questions can achieve complete student learning. Novelty/Originality of this study: The novelty of this research is to determine the effectiveness of applying cooperative learning techniques for sending greetings and questions to achieve complete chemistry learning in chemical bonding material.